Exercise Therapy Videos Development as Alternative Physiotherapy Learning Media - Aqobah, Qory Jumrotul; Rahayu, Ayu (Department of Physical Education, Sport, Health and Recreation, 2022)
Physiotherapy is one of the compulsory courses organized by the Sports Science study program. The observation results on learning facilities show that the media used for Physiotherapy courses is still very limited. This development research aims to produce a learning product in the form of learning videos and several quality theories that are suitable to use and can be an alternative learning media in Physiotherapy courses. The method used in this research is the Research & Development (R&D), which refers to the 4D model consisting of 4 stages includes define, design, develop, and disseminate. The results of this research are in the form of video-based learning media, which have advantages such as presenting the material and making applications that can be downloaded on the Android system. The validity test results obtained a score of 93% from the expert validators. The effectiveness aspects of learning outcomes obtain good criteria based on the results of learning tests with the 83% completeness percentage, so it can be concluded that the developed video-based learning media in exercise therapy has a good effect on students’ learning outcomes. Overall, the percentage of students’ completeness tests reached a score of > 75%.